Metastatic Liposarcoma: A Cause of Symptomatic Acute Pericarditis. (1997) - Hatton, Matthew Q. F.; Reid, Robin; Barrett, Ann
Abstract : We describe a patient presenting with a myxoid liposarcoma of the lower thigh in whom an episode of acute pericarditis indicated the recurrence of widespread metastatic disease.